The princess diarist [compact disc, unabridged] - Fisher, Carrie (Penguin Audio, 2016)
From Princess Leia herself: another brilliantly hilarious self-examination of her unlikely life and times. A thoroughly original and intimate memoir by the bestselling author of Postcards from the Edge and Wishful Drinking.